Ocena nevropsihološkega statusa in njen pomen v procesu kompleksne rehabilitacije - Bras, Nina (Rehabilitacija (Ljubljana), 2013)
Background: Neuropsychological screening is important in many clinical fields, including vocational rehabilitation. We have started to use the RBANS (Repeatable Battery for the Assessment of Neuropsychological Status) at the University Rehabilitation Institute in Ljubljana for this purpose. The RBANS addresses five fields of abilities: immediate memory, visuospatial/constructional, language, attention, and delayed memory. Methods: Our preliminary study involved 36 participants who were included in interdisciplinary team treatment within the health care programme at the Centre for Vocational Rehabilitation of our Institute. In addition to the RBANS scores, primary diagnosis, associated psychopathology and rehabilitation outcomes were analysed. Results: The RBANS tests exhibited a medium difficulty level, except the tests of attention (which proved to be the most difficult for the participants) and the tests that measure visual spatial and constructional abilities (which proved to be less difficult for the participants). Among the primary diagnoses, traumatic brain injury and neurological diseases were the most prevalent. Associated psychopathology varied greatly and the number of mental disturbances also varied between the participants. The most commonly suggested rehabilitation outcomes were part-time employment, retirement, extended sick-leave and inclusion into our vocational rehabilitation programme (acquiring additional qualifications through adult education). Conclusions: The RBANS test battery proved to be useful for screening purposes and individual clinical use in vocational rehabilitation. Further research will be needed to establish its prognostic usefulness in terms of predicting the rehabilitation outcome.
Keywords: Neuropsychological tests; neuropsychology; nevropsihologija; nevropsihološki testi; poklicna rehabilitacija; presejalni postopki; rehabilitacija; Rehabilitation, Vocational; screening; testna baterija RBANS; The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS); vocational rehabilitation